The Effect of Coconut Water Against Decreasing Dehydration Degrees in Children Ages 5-10 Years with Diare - Nita Dwi Astikasari (Humanistic Network for Science and Technology (HNST), 2017)
Dehydration is a disturbance in the fluid or water balance in the body. This occurs because the water outlays more than the income (e.g. drinking). This loss of body fluid is accompanied by electrolyte balance disorders of the body. In Coconut Water contain content such as protein, fat, carbohydrate and Mineral. Mineral content which is high enough in Coconut Water that is 91% can fulfill requirement of human collapsed liquid that lost during dehydration take place. The purpose of this study is to determine the effect of coconut water to decrease degree of dehydration in children aged 5-10 years with diarrhea. The design of this study was pre-experimental by using one group pretest-posttest. In this type of study revealed causal relationships involving one group of observational subjects, before intervention and then observed again after intervention. From total of 14 respondents, before giving coconut water 9 respondents experienced Dehydration Moderate and 5 respondents experienced mild dehydration, and after giving coconut water from 9 respondents who experienced dehydration down to mild dehydration and 5 respondents experiencing mild dehydration down to no dehydration. The result of data analysis with Wilcoxon test at α = 0.05 got the result of statistical test with significance value 0.000.Adanya Influence of Coconut water to decrease degree of dehydration in children aged 5-10 years with diarrhea in Tales Village Ngadiluwih District. Coconut water containing a lot of electrolytes can lower the degree of dehydration because by drinking coconut water can replace the electrolytes in the body lost during diarrhea. Keywords: Coconut water, Dehydration, Childre